Manganese oxidation counteracts the deleterious effect of low temperatures on biofilm formation in Pseudomonas sp. MOB-449 - Ciancio Casalini, Lucila; Piazza, Ainelen; Masotti, Fiorella; Garavaglia, Betiana S.; Ottado, Jorgelina; Gottig, Natalia (Frontiers in Molecular Biosciences, 2022)
Mn removal from groundwater by biological sand filter technology is negatively impacted by low temperatures in winter periods. Therefore, the need to study Mn(II)-oxidizing bacteria (MOB) having the potential to oxidize Mn(II) and form biofilms at low temperatures is imperative. These MOB can have potential as inocula for sand filter bioaugmentation strategies to optimize Mn removal during winter periods. We previously showed that a Pseudomonas sp. MOB-449 (MOB-449), isolated from a Mn biofilter, oxidizes Mn(II) in a biofilm-dependent way at low temperatures. In this work, MOB-449 Mn(II) oxidation and growth capacities were evaluated under planktonic and biofilm conditions at different temperatures. At 18°C, MOB-449 showed enhanced biofilm formation due to the addition of Mn(II) to the medium correlating with Mn(II) oxidation, compared to biofilms grown in control medium. Moreover, this enhancement on biofilm formation due to the addition of Mn(II) was only observed at 18°C. At this temperature, Mn(II) oxidation in membrane fractions collected from biofilms was induced by uncoupling oxidative phosphorylation from the electron transport chain with 2,4-Dinitrophenol. In Pseudomonas, a role for c-type cytochrome in Mn(II) oxidation has been demonstrated. Accordingly, transcriptional profiles of all terminal oxidases genes found in MOB-449 showed an induction of cytochrome c terminal oxidases expression mediated by Mn(II) oxidation at 18°C. Finally, heme peroxidase activity assays and MS analysis revealed that PetC, a cytochrome c5, and also CcmE, involved in the cytochrome c biogenesis machinery, are induced at 18°C only in the presence of Mn(II). These results present evidence supporting that cytochromes c and also the cytochrome c terminal oxidases are activated at low temperatures in the presence of Mn(II). Overall, this work demonstrate that in MOB-449 Mn(II) oxidation is activated at low temperatures to gain energy, suggesting that this process is important for survival under adverse environmental conditions and contributing to the understanding of the physiological role of bacterial Mn(II) oxidation.